Pengaruh Konsentrasi Tepung Wortel (Daucus carota) Pada Pakan Terhadap Peningkatan Warna Ikan Maskoki (Carassius auratus) - Riki MS Karo-Karo; Syammaun Usman; Irwanmay Irwanmay (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Maskoki fish (Carassius auratus) is a type of fish that have other names which have a gold fish body shape ranging from red, yellow, green, black and silvery. As fish are included in the category of ornamental fish, then to produce the best maskoki fish, needed a good environment and foods high in nutrients. Good food nutrition will support color, good health. Color is one of the reasons ornamental fish demand by the public, so farmers need to retain the color of ornamental fish in particular by giving feed containing pigment. The work done to obtain a uniform bright colors in fish is added to the pigment in the feed source. Source of natural pigments can be obtained from flour carrot (Daucus carota). The purpose of this study was to determine the dose of carrot flour that can enhance the color of maskoki fish. This study used a completely randomized design (CRD) with three replications, with doses of 0%, 1%, 3%, and 5% for 30 days. The addition of carrot powder through the feed can improve the color of maskoki fish. Giving carrot flour with a dose of 5% produces a brighter color than the other doses. Carrots Flour Addition on the feed had no effect on the weight and length maskoki goldfish.Keywords: Carassius auratus, maskoki fish, Daucus carota, color